Assessment of Knowledge, Attitudes and Practices of Health-Care Providers about Biomedical Waste Management in Primary Health Centers in Erbil City (Journal of Pharmaceutical Negative Results, 2022)
Medical waste is infectious, contain toxic chemicals and pose contamination risks to both people and also the environment in primary health care centers. In the present study, we assessed the knowledge, attitude and practices of health care providers about biomedical waste management in primary health care centers PHCC in Erbil district center, Kurdistan Iraq. Using a self-administered questionnaire, we collected data on biomedical waste management from samples of health care providers (HCP) in 25 health centers in the Erbil district center. Based on results, total knowledge, and attitude and practice scores on a 34 questions was prepared related to Knowledge, attitude and practice. Total 687 HCP participated in study and largest proportion of the sample (40.9%) were aged 41-50 years, more than half (58.4%) were females, nurses constituted 41.5% of the sample, 39.9% were diploma certificate holders, The majority of the sample had more than 10 years of experience, but only 10.8% 74 of them had received training about biomedical waste management. Almost all the participants had no strong knowledge about biomedical waste (BMW) management, and very little (less than 10%) had moderate knowledge. More than 90% of the sample had no information about the weakest and strong microbes resistant to antiseptics, the majority 525 (76.4) have little knowledge about importance to taking the vaccination hepatitis B and C to prevent from BMW hazardous, the majority (93.3%) of the participants believe that safe disposal of BMW is extremely important to prevent infection transmission, more than two thirds (69.9%) of the participants always dispose sharps in puncture proof container. Conducting of appropriate training on how to dealing with biomedical waste is essential to develop safe practices among HCP.